Immunoglobulin replacement therapy in patients with primary and secondary immunodeficiencies: impact of infusion method on immunoglobulin-specific perceptions of quality of life and treatment satisfaction - Rajiv Mallick; Noemi Hahn; Christopher Scalchunes (Allergy, Asthma & Clinical Immunology)
Abstract Background Immunoglobulin replacement therapy (IgRT) is the current standard of care for primary antibody deficiency patients (majority of all primary immunodeficiency (PID) diseases), with growing real-world evidence supporting use for secondary immunodeficiency (SID) patients. Infusion methods and practices can affect patients’ satisfaction with their treatment and perception of their health-related quality of life. Methods An online survey of US patients with PID and SID was conducted. This research investigates primarily the impact of two IgRT infusion methods, intravenous immunoglobulin therapy (IVIG) and subcutaneous immunoglobulin (SCIG), on the patient reported outcome (PRO) Life Quality Index (LQI) tool. Patient reported infusion time efficiency, physical and mental health (PROMIS GPH-2 and PROMIS GMH-2 respectively), patient acceptability of their symptom state (PASS), upper extremity disability (Quick DASH) and general health perception (via the GHP) are also investigated. Results Responses of 990 patients (391 IVIG and 598 SCIG) were analyzed. The median total LQI score amongst SCIG patients (84.7) was higher than IVIG patients (81.9) (p < 0.001), and was significantly higher on 3 out of 4 sub-domains of the LQI. SCIG patients scored higher on items that are related to convenience and reported less interference with everyday life: “Are convenient”, “Are scheduled according to my convenience”, “Do not interfere with my work/school” and “Require very little time and cost”. However, there was no significant difference between the two patient cohorts on other, non-IG specific PROs (PASS, PROMIS GPH-2 and GMH-2 and Quick DASH). Patient reported time per infusion was lower for SCIG infusions than IVIG infusions (pre-infusion time; 22 min vs. 63 min, p < 0.001, infusion time; 120 min vs. 240 min, p < 0.001, post-infusion time; 9 min vs. 31 min, p < 0.001). IVIG patients also reported more interference with everyday life than SCIG patients (82 vs. 86, p < 0.001). Conclusions The significantly higher LQI scores for patients receiving SCIG than those receiving IVIG confirms existing evidence that substitution of SCIG for IVIG may favorably impact immunoglobulin specific perceptions of quality of life and treatment satisfaction for appropriately selected patients. Our evidence on infusion times indicates similar improvement may be possible on infusion time efficiency.